Analisis Potensi Sektor Ekonomi sebagai Penunjang Pertumbuhan Ekonomi Kabupaten Boalemo - Anggita Permata Yakup (Universitas Gorontalo, 2019)
Determination of potential sectors becomes important as a basis for regional development planning in accordance with the era of regional autonomy, in the era of regional autonomy each region competes to increase regional economic growth, in order to increase the prosperity of its people This article examines the potential of the economic sector as supporting economic growth based on the 2010-2016 in time series data. This article uses the Shift Share, LQ, and Typology Matrix analysis method. The results show that the agricultural sector is a potential or very dominant sector because it shows enormous growth and contribution to the formation of RGDP and development in Boalemo district..